2004
DOI: 10.1037/0735-7044.118.3.597
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric Specialization in the Primary Auditory Area of Awake and Anesthetized Starlings (Sturnus vulgaris).

Abstract: Although evidence exists for a lateralization of song production, few studies have focused on the perceptual aspect of lateralization in songbirds. In the present study, the authors recorded neuronal responses to a variety of species-specific and artificial, nonspecific stimuli in both hemispheres of awake and anesthetized male starlings (Sturnus vulgaris). Recordings were made in the primary auditory area of the songbird brain, the Field L complex. The right hemisphere exhibited significantly more responsive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 50 publications
3
27
2
Order By: Relevance
“…Bilateral asymmetry with either left-sided or right-sided dominance, or differential dual specialization, has been previously observed in songbirds in relation to both central and peripheral control of song production (49)(50)(51)(52). As far as song perception is concerned, increased neuronal responsiveness to behaviorally relevant song stimuli has been observed in the field L complex and HVC on the right side in starlings (53,54). Right hemispheric specialization is seen only in awake birds.…”
Section: Familiar Song Stimuli Show Selective Differential Topographymentioning
confidence: 83%
“…Bilateral asymmetry with either left-sided or right-sided dominance, or differential dual specialization, has been previously observed in songbirds in relation to both central and peripheral control of song production (49)(50)(51)(52). As far as song perception is concerned, increased neuronal responsiveness to behaviorally relevant song stimuli has been observed in the field L complex and HVC on the right side in starlings (53,54). Right hemispheric specialization is seen only in awake birds.…”
Section: Familiar Song Stimuli Show Selective Differential Topographymentioning
confidence: 83%
“…Using three alcohols and one binary mixture as odourants, we found that odour processing is asymmetric: the neural odour representations were more separated in the right AL, and bees with only their right antenna in use were better in segregating a target odour from a background odour in a cross-adaptation experiment. Similarly, in vertebrates the discriminatory power of sensory representations can be lateralized, as has been shown in the visual system of birds [27][28][29][30][31] both behaviourally and physiologically (fMRI during a discrimination task described in [31], electrophysiological recordings in the primary auditory area in [30] and in the auditory system of bats [32]; the latter was revealed by measuring inter-stimuli Euclidean distances).…”
Section: Discussionmentioning
confidence: 99%
“…In order to test this hypothesis (see also George et al, 2004) we counted, at each recording site, the number of stimuli that produced an activation. We could then have an idea of the level of neuronal specialization in these diVerent sub-areas.…”
Section: Comparisons Withmentioning
confidence: 99%